Aerobic oxidation catalyzed by polyoxometalates associated to an artificial reductase at room temperature and in water. Issue 12 (14th May 2020) - Naim, Ahmad; Chevalier, Yoan; Bouzidi, Younes; Gairola, Priyanka; Mialane, Pierre; Dolbecq, Anne; Avenier, Frédéric; Mahy, Jean-Pierre
Abstract : Four polyoxometalates (POMs) were combined with an artificial reductase based on polyethyleneimine (PEI) and flavin mononucleotide (FMN) which is capable of delivering single electrons upon addition of nicotinamide adenine dinucleotide (NADH). Abstract : Four polyoxometalates (POMs) were combined with an artificial reductase based on polyethyleneimine (PEI) and flavin mononucleotide (FMN) which is capable of delivering single electrons upon addition of nicotinamide adenine dinucleotide (NADH). The efficiency of this system for sulfoxidation reactions in water, at room temperature, under atmospheric pressure and with dioxygen as an oxidant was demonstrated, with yields up to 82% in sulfoxide. Mechanistic investigations allowed proposing two different catalytic pathways, depending on the nature of the POM. For the polyoxotungstates Na12 [(ZnW9 O34 )2 WZn3 (H2 O)2 ]·46H2 O and Na7 K7 [(PW9 O34 )Ni3 (OH)(H2 O)2 (Ale)2 Ni]·34H2 O (Ale = alendronate = [O3 PC(O)(C3 H6 NH3 )PO3 ] 4− ), the in situ production of H2 O2 by the artificial reductase that activates the POM was evidenced. Alternatively, for the polyoxomolybdates H3 [PMo12 O40 ]·14H2 O and H4 [PMo11 VO40 ]·14H2 O, the reduction of the POM by the artificial reductase, followed by the reductive activation of O2, led to the sulfoxidation reaction.